Sociodemographic Correlates of Choice of Health Care Services in Six Rural Communities in North Central Nigeria - Onyemocho Audu; Ishaku Bako Ara; Abdujalil Abdullahi Umar; Victoria Nanben Omole; Solomon Avidime (Hindawi Limited, 2014)
Household expenditure on health has increasingly remained a major source of health care financing in Nigeria despite the introduction of several social health scheme policies provided by the government for meeting the health care costs of patients. Recognizing these limitations, this study assessed the type of health care services people commonly use in various illnesses and the sociodemographic correlates of the preferred health care services by household heads in six rural communities of North Central Nigeria. A cross-sectional community-based descriptive study design was used to study 154 household heads in the settlements using a multistage sampling method. Multiple logistic regressions were performed to investigate independent predictors that had significant chi-square at P<0.05. The leading causes of illness experienced by respondents were medical conditions (42.0%) and 41.7% of them sought treatment from patent medicine vendors. The dominant reasons for health-seeking preferences were financial access (53.7%) and proximity (48.6%). Age had a higher impact (Beta = 0.892) on the health-seeking preferences of the respondents as compared to their occupation and religion (Beta = 0.368 and −0.746, resp.). Therefore, in order to meet the health care of patients, it is pertinent that the unmet needs of patients are properly addressed by appropriate agencies.